2008
DOI: 10.1007/s11064-008-9886-3
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Delayed Consequences of Xanomeline Wash-Resistant Binding at the M3 Muscarinic Receptor

Abstract: Xanomeline is thought to be a M1/M4 functionally selective agonist at muscarinic receptors. We have previously demonstrated that it binds in a unique manner at the M1 receptor. In the current study, we examined the ability of xanomeline to bind to the M3 receptor and determined the long-term consequences of this mode of binding in Chinese hamster ovary cells expressing M3 receptors. Xanomeline binds in a reversible and wash-resistant manner at the M3 receptor and elicits a functional response under both condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…Since xanomeline is not entirely M 1 /M 4 -specific (Jakubík et al, 2006;Noetzel et al, 2009), classical cholinomimetic side effects, e.g., gastrointestinal side effects, were observed in humans (Bodick et al, 1997;Shekhar et al, 2008). Previous efforts to develop highly selective orthosteric agonists of the individual muscarinic subtypes have not been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Since xanomeline is not entirely M 1 /M 4 -specific (Jakubík et al, 2006;Noetzel et al, 2009), classical cholinomimetic side effects, e.g., gastrointestinal side effects, were observed in humans (Bodick et al, 1997;Shekhar et al, 2008). Previous efforts to develop highly selective orthosteric agonists of the individual muscarinic subtypes have not been successful.…”
Section: Discussionmentioning
confidence: 99%
“…1 a and b, respectively). Once again, this is in contrast to the effects of xanomeline under similar conditions whereby inhibition of [ 3 H]NMS binding results in a biphasic curve and reaches a maximum of nearly 100% [13] . Previous research demonstrated a decrease in protein content following xanomeline pretreatments at the M1 receptor [14] .…”
Section: Comparison Of the Effects Resulting From Brief And Long-termmentioning
confidence: 74%
“…Binding occurs in a reversible manner at the orthosteric (primary) binding site and in a wash-resistant manner at an allosteric (secondary) binding site [12] . We have demonstrated that this unique binding profile also occurs at the M3 receptor [13] . At both the M1 and M3 receptors, wash-resistant xanomeline binding leads to a long-term decrease in cell-surface receptor expression and attenuation of receptor function [13,14] .…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations